The evil inclination in early Judaism and Christianity - Aitken, J. K.; Patmore, Hector M. ca. 20./21. Jh.; Rozen-Tsevi, Yishai (Cambridge University Press, 2021)
Introduction / J.K. Aitken, H. Patmore and I. Rosen-Zvi -- Reconsidering the semantics of the "inclination" (yéṣer) in classical biblical Hebrew / Noam Mizrahi -- The "inclination" (yēṣer) as rendered in the Septuagint / James K. Aitken -- "Fleshly spirit" and "vessel of flesh" in 4Qinstruction and the thanksgiving hymns / Benjamin Wold -- Theological anthropology in the Enochic tradition / Loren Stuckenbruck -- The perils of philosophical persuasion : Philo on the origin of moral evils / Sharon Weisser -- The evil inclination (yeṣer ha-ra') in Tannaitic literature : demonic desires and beyond / Ishay Rosen-Zvi -- Conflicting intrapersonal powers in Paul's letters / Daniel Schumann -- The "two inclinations" and the double-minded human condition in the letter of James / George van Kooten -- An evil inclination in early targums to the Pentateuch and prophets? / Hector M. Patmore -- "Gnostic" theologies of evil / Timothy Pettipiece -- The rabbinic "inclination" (yeṣer) and the Christian Apocrypha / Monika Pesthy-Simon -- Origen on the origin of sin / Riemer Roukema -- Augustine on the diabolical suggestion of sin / Sophie Lunn-Rockliffe -- Jerome and the "inclination" (yeṣer) : the evidence of the Vulgate / C.T.R. Hayward -- Rabbinic inclinations and monastic thoughts : Evagrius Ponticus' doctrine of reasoning (logismoi) and its antecedents / Augustine Casiday -- "Inclination" (yaṣrā) in the Syriac tradition / David G.K. Taylor -- Evil, sin and inclination (yeṣer) in Jewish and Christian poetic disputes between the body and soul / Ophir Münz-Manor -- The Wizard of Az and the evil inclination : the Babylonian rabbinic inclination (yeṣer) in its Zoroastrian and Manichaean context / Yishai Kiel -- The evil inclination in the targums to the writing / Leeor Gottlieb.